"Then they prayed, they did nothing else, they just prayed for the boy and he was well": A qualitative investigation into the perceptions and behaviours surrounding snakebite and its management in rural communities of Kitui county, Kenya. - Leo Wood; Cecilia Ngari; Stanley Parkurito; Kieran Barnes; Denis Otundo; Daniel Asiago Misiani; Geoffrey Maranga Kephah; Anna Trelfa; George O Olouch; Robert A Harrison; Frank-Leonel Tianyi (Public Library of Science (PLoS), 2022)
Introduction Human-snake interactions are common in tropical regions where subsistence-farming and livestock-herding activities predominate alongside proliferation of snakes. Local beliefs and perceptions about snakes and snakebites influence human behaviour. Understanding these beliefs and perceptions can inform the development of resources to drive behaviour change and to minimise the risk of injury to both humans and snakes. This qualitative study, conducted between May and July 2019, sought to explore the beliefs and perceptions regarding snakes and snakebites, and methods of prevention and management among members of the community in Kitui County, Kenya. Methods Semi-structured interviews were used to collect qualitative data from 23 participants, recruited using a stratified purposeful sampling strategy in four selected sub-counties of Kitui county. Interview data was anonymised and coded and a thematic analysis was conducted using NVivo 12. Results People from Kitui county mostly had negative perceptions about snakes. There was a generalised awareness of the need to prevent snakebite, predominantly through keeping snakes away from homes/compounds. However, implementation was limited by financial constraints. Participants also identified logistic and financial obstacles to early hospital presentation following a snakebite, and they expressed a strong preference of having their snakebites treated in a hospital over consulting traditional healers. There was a universal recognition of the benefit of early intervention with a specific appreciation of the utility of the black stone. Furthermore, the removal of a snake's "teeth" was an expected treatment outcome for some community members, with the failure to do so perceived as causing poor wound healing or persistence of symptoms. Some religious groups held views which differed from most participants. Conclusion There is a need to explore and clarify common misconceptions about snakes and first aid treatment of snakebites, encourage learning about the true nature of snakes, and highlight beneficial uses of snakes. A change in the epistemological conception of community education material by enhancing the value and use of local forms of knowledge, and the employment of art techniques to transmit this knowledge, could improve community perception and methods of snakebite prevention. Patient expectations should be appropriately managed by discussing possible outcomes, incorporating follow-up visits and addressing long-term complications of snakebites.